PENGGUNAAN EKSTRAK DAUN SIRIH (Piper betle Linn) UNTUK MENGHAMBAT BAKTERI Aeromonas hydrophila DAN TOKSISITASNYA PADA IKAN PATIN (Pangasius hypophthalmus) - Siti Aisiah; Muhammad Muhammad; Anita Anita (Fish Scientiae, 2019)
This research was aimed a finding the part of Piper betle Linn which had thebiggest resistance to Aeromonas hydrophila bacteria and to know the minimal concentrate which could obstruct the growth of A. hydrophila bacteria and to know effective concentrate toxicity of P. betle Linn to Pangasius hypophthalmus. Therandom sampling used proportionate stratified random sampling. In toxicity test, it had be done 4 treatment, which was given to fish, those were : A = fish was injected with 25 % concentrate of extract P. betle Linn leaves, B = fish was injected with 75% concentrate of extract P. betle Linn leaves, C = positive control (fish was injected with sterile aquadest), and D = negative control (fish wasn’t injected) and 3 trial.Sensivity result of A. hydrophila bacteria to P. betle Linn showed that the axtract of Piper betle Linn leaves-methanol had bigger activity than others. Depended on MICtest of the leaves P. betle Linn-methanol extract showed result that the extract had25% minimal bloked concentrate to A. hydrophila bacteria. The result of toxicity testof P. betle Linn 75% and 25% leaves was no mortality 50% of P. hypophthalmus.Water quality parameter during experiment like dissolving oxygen, pH, ammonia,CO2, and temperature were still in reasonable range for Pangasius hypophthalmus.